THE EFFECT OF HOLLOW SPRINT AND SPRINT TRAINING ON LONG JUMP SKILLS - Aisah R. Pomatahu (Sport Scientific And Practical Aspects, 2025)
This experimental, field research is to find out whether or not both the hollow sprint and sprint training affect long jump skills and to explore the difference of the effects of these two types of training. Furthermore, the design of this study consisted of two tests, namely pre-test and post-test.The sample involved 20 students of public junior high school SMPN 4 Gorontalo, Indonesia. The results show that both hollow sprint and sprint training affects the students’ long jump skills. In addition, there is no significant difference regarding the effect of both trainings on the students’ skills in such an athletic sport.